PERFORMA SAPI FRIESIAN HOLSTEIN DI SUMBERBULU DAIRY FARM BANYUWANGI JAWA TIMUR - ., WIRANDO; DOLOKSARIBU, L.; DEWANTARI, M.; KAYANA, I. G. N.; MAHARDIKA, I. G. (Majalah Ilmiah Peternakan, 2023)
Every dairy farm should keep records of bloodlines, pests, disease, feed types and consumption. These records help preventing inbreeding, control pests and disease and provide the best feed for optimum performance. Howe- ver, smallholder dairy farmers in Indonesia pay less attention on the benefits of recordings. The purpose of this study is to analyse the reproductive and productive performance recorded of the productivity of FH cattle at Sum- berbulu Dairy Farm. An ex-post facto Comparative Causal method was used, where data were obtained by observa- tions, interviewed the owner, and recorded all available archives from December 2021 to January 2022 supporting the data analysis. Data of reproductive and productive performance were analysed by using simple descriptive anal- ysis. The results showed their S/C, days open, gestation period, and calving interval were 2.15 ± 0.28 times, 113.68 ± 18.05 days, 280.10 ± 2.41 days, and 393.33 ± 15.27 days, respectively. The total milk production 3.411.8 ± 170.03 kg/cow/lactation, MPPA 3.946 ± 42.24 kg/lactation, length of lactation period 270.03 ± 14.24 days, and length of dry period 94.24 ± 7.98 days. The reproductive and productive performance of FH dairy cows reared at Sumberbulu Dairy Farm were in ideal standard of FH cows reared in tropical areas.